Comparative study of individualized 3D-printing navigation technology and free-hand isthmus method in lumbar CBT screw implantation - Hu, Hanlin; Lu, Zhenghao; Gao, Xiaowen; Ou, Jun; Wang, Jiong (Frontiers in Surgery, 2025)
ObjectivesTraditional cortical bone trajectory (CBT) screws in the lumbar spine offer greater holding strength and are well-suited for patients with osteoporosis. However, the screw implantation procedure is challenging and associated with significant risk. This study aimed to assess whether individualized 3D-printing navigation technology provides higher accuracy and better clinical outcomes compared to the free-hand isthmus method for lumbar CBT screw implantation.MethodsFrom September 2020 to August 2023, a total of 41 patients who underwent CBT screw surgery were retrospectively collected. Among them, 23 patients underwent the free-hand isthmus method (Group A), while 18 patients underwent the individualized 3D-printing navigation technique (Group B). All imaging and clinical data for these patients were collected in a blinded manner.ResultsDuring the surgery, 185 CBT screws were implanted into the lumbar spines of 41 patients—78 in Group A and 107 in Group B. After the surgery, the majority of implanted screws (86.5%) were classified as grade 0, indicating satisfactory implantation. Compared to Group A, Group B had fewer screws classified as grade 1 or grade 2 (p = 0.045), indicating higher accuracy in screw implantation. Additionally, Group B also had a shorter operation duration (p = 0.02), fewer fluoroscopy exposures (p < 0.01), and less blood loss (p = 0.03). In addition, compared to Group A, individuals in Group B showed significant improvement in back pain symptoms at both 3 and 6 months (p = 0.01 and <0.01), as well as in physical activity at 3 months (p = 0.02) postoperatively. No significant difference in postoperative complications was observed between the two groups.ConclusionCompared to the free-hand isthmus method, lumbar CBT screw implantation with individualized 3D-printing navigation technology shows higher accuracy, shorter operative time, reduced intraoperative fluoroscopy and blood loss, and better clinical outcomes at three months post-surgery.